Effect of Breastfeeding and Preterm Births on the Severity of Lower Respiratory Tract Infections and Associated Risk of Hospitalization in Infants and Toddlers - And Demir MD, PhD, MBA; Nihal Özdemir Karadas MD; Ulas Karadas MD (SAGE Publishing, 2022)
We studied the effect of duration of breastfeeding and history of prematurity on the duration of hospitalization in infants with lower respiratory tract infections (LRTI) because these may reflect the severity of illness as well as sizable direct and indirect healthcare costs. One hundred twenty-five patients (49 girls, 76 boys; aged 1-24 months) were hospitalized for LRTI during a period of 102 days and studied prospectively. We found a significant difference ( P = .045) between the durations of hospitalization of the 92 patients breastfed for at least six months, compared to the other group of 33 patients who were breastfed for less than six months. The durations of hospitalization among the groups with and without a history of prematurity were not statistically different ( P = .78). A history of breastfeeding for more than six months had significant effect on the duration of hospitalization, but this was not true for children with a history of preterm birth.